Analisis Pengaruh Asset Growth (AG), Total Asset Turn Over (TATO), Dan Price Book Value (PBV), Terhadap Harga Saham Perusahaan Pada Jakarta Islamic Index - Nur Ahmadi Bi Rahmani (Jurnal Riset Akuntansi dan Bisnis, 2021)
The purpose of this study is to analyze the Analysis of the Effect of Asset Growth (AG) Total Asset Turn Over (TATO), and Price Book Value (PBV), on the Company's Stock Price on the Jakarta Islamic Index for the 2016-2020 period. This study uses a quantitative approach with secondary data. The data analysis technique used in this study is using multiple linear regression analysis techniques, where Asset Growth (AG), Total Asset Turn Over (TATO), and Price Book Value (PBV) as independent variables and Stock Price as the dependent variable with analytical tools. data processing using SPSS 24.0. Based on the results of the analysis, the findings in this study indicate that partially Asset Growth (AG) has a significant effect on stock prices. The results of the next study partially Total Asset Turn Over (TATO) has a significant effect on stock prices. Price Book Value (PBV) has an effect and is significant on stock prices. Simultaneously Asset Growth (AG) Total Asset Turn Over (TATO), and Price Book Value (PBV) affect the price.